Combination of phosphotidylinositol‐3‐kinase targeting with cetuximab and irradiation: A preclinical study on an orthotopic xenograft model of head and neck cancer. Issue 1 (10th August 2016) - Bozec, Alexandre; Ebran, Nathalie; Radosevic–Robin, Nina; Chamorey, Emmanuel; Yahia, Hedi Ben; Marcie, Serge; Gautier, Mathieu; Penault–Llorca, Frédérique; Milano, Gérard
Abstract: Background: The purpose of this study was to investigate the effects of combining the phosphotidylinositol‐3‐kinase (PI3K) inhibitor buparlisib (BKM)120 with the anti‐epidermal growth factor receptor (EGFR) agent cetuximab and radiotherapy (RT) on an orthotopic model of head and neck squamous cell carcinoma (HNSCC). Methods: We evaluated the antitumor efficacy of BKM120, cetuximab, and RT, administered alone or in combination, using the human PIK3CA‐mutated HNSCC cell line, CAL33, injected into the floor of the mouth of nude mice. Results: Compared with control, the BKM120‐cetuximab and the BKM120‐cetuximab‐RT combinations led to the highest tumor inhibition ( p < .001). The highest inhibitory effect of treatments on cell proliferation, mitogen‐activated protein kinase (MAPK) and PI3K/protein kinase B (AKT)/mammalian target of rapamycin (mTOR) signaling pathways were found with the BKM120‐cetuximab association. The association of BKM120 and cetuximab with RT inhibited RT‐induced activation of the MAPK pathway. Conclusion: These results can serve as a preclinical rationale for innovative treatments combining PI3K inhibition with anti‐EGFR therapies and irradiation in patients with HNSCC. © 2016 Wiley Periodicals, Inc. Head Neck 39: 151–159, 2017